Lifestyle Characteristics and Gastroesophageal Reflux Disease: A Population-Based Study in Albania - Lulzim Çela; Bledar Kraja; Kliti Hoti; Ervin Toçi; Herion Muja; Enver Roshi; Genc Burazeri (Gastroenterology Research and Practice)
Aim. We aimed to assess the prevalence and lifestyle correlates of gastroesophageal reflux disease (GERD) in the adult population of Albania, a Mediterranean country in Southeast Europe which has experienced major behavioral changes in the past two decades. Methods. A cross-sectional study, conducted in 2012, included a population-representative sample of 845 individuals (≥18 years) residing in Tirana (345 men, mean age: ; 500 women, mean age: ; response rate: 84.5%). Assessment of GERD was based on Montreal definition. Covariates included socioeconomic characteristics, lifestyle factors, and body mass index. Logistic regression was used to assess the association of socioeconomic characteristics and lifestyle factors with GERD. Results. The overall prevalence of GERD was 11.9%. There were no significant sex differences, but a higher prevalence among the older participants. In fully adjusted models, there was a positive relationship of GERD with smoking, physical inactivity, fried food consumption, and obesity, but not so for alcohol intake and meat consumption. Conclusion. We obtained important evidence on the prevalence and lifestyle correlates of GERD in a Western Balkans' country. Smoking, physical inactivity, and obesity were strong “predictors” of GERD in this population. Findings from this study should be replicated in prospective studies in Albania and other transitional settings.